Prospective Deficiency Symptoms of Iron-Folate in Expecting Women, A Clinical Study - Kamran Arzoo, Jazib Andleep, Hasan Akbar Khan, Fakharunissa, Shahnaz Bano Memon, Madiha Afzal, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out importance of folic acid and iron uncovered in pregnant women and physiological complications. Period of study: The Study was conducted from January 2022 to May 2022 in different medical institutes. Methods: For current study 400 women with 29-38 weeks pregnancy (third trimester) were selected and divided them into three different groups. In group-A 100 women were those how were taking regularly folic acid and iron from their pregnancy preparation till to day and in group-2, 150 pregnant women were those how started folic acid and iron in third trimester. Whereas in group-3 150 pregnant women were not taking folic acid and iron regularly. The raw data of all medical complications of individuals were presented Bio-statistically with the application of SPSS. Results: Folic acid levels, hemoglobin levels, weakness, headache, fatigue, pale skin color, shortness of breath, mouth ulcer, disturbed vision, memory lost were measured in mothers of three groups. Whereas Diarrhea, Decreased appetite, short of breath and neural tube defects were observed in delivered new born babies by these women. It was concluded by comparing results of each group that study was significant, and a remarkable significant changes (p<0.05)were seen in the individuals of three groups. Conclusion: Folic acid and iron have a key role for the better health of both mother and new born baby. Folic acid deficiency anemia and decreased biosynthesis of hemoglobin because of iron deficiency caused serious medical complications in mother as well as in fetus.